PENGARUH ARUS KAS OPERASI, LIKUIDITAS, LEVERAGE, DIVERSIFIKASI, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS (Studi empiris pada perusahaan sektor aneka industri yang terdaftar di BEI 2014-2016) - Febriyan Febriyan, Ari Hadi Prasetyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
Recent era technology development escalate competition among companies. Most companies that unable overcome competion will not maximaze their profit, even tend to experience operating loss and the other side put the firm into financial distress. This research aims examine whether cash flow from operation, liquidity, leverage, diversification, and size are predictors that can be use to analyze companies financial distress. The sample of this research are 22 company related to various industry sector listed on IDX for year 2014-2016, the sample obtained is 66 companies. Stattistical technic analysis used are descriptive analysis, pooling test, logistic regression test , Hosmer and Lemeshowâ€™s Goodness, Wald Test, -2 Log Likelihood test, and Nagelkerkeâ€™s R Square test. The data collected from secondary data, downloaded from www.idx.co.id. The research results shows that there is not enough evidence that cash flow from operation, liquidity, diversification, and size give significant effect to financial distress of company. While leverage have enough evidence gives significant effect with positive direction to the possibilty of financial distress of a company.Â Keywords : Cash Flow From Operation, Liquidity, Leverage, Diversification, Size, and Financial Distress